Proceso de atención de enfermería pediátrico con diagnóstico de hidronefrosis bilateral grado I - Cervantes Santana, Patricia Yomira (2018)
The pathology Bilateral hydronephrosis is one of the most common problems in the kidneys continues to represent a serious problem of kidney failure, is found more often in children during childhood, was diagnosed during pregnancy by prenatal ultrasound and in older adults and by It makes difficult the correct elimination of diuresis. This clinical case calls nursing interventions based on the process of pediatric nursing care with a diagnosis of Grade I Bilateral Hydronephrosis. It was carried out with the objective of carrying out, evaluating through the NANDA, NOC and NIC taxonomies and educating the relatives with respect to to the activities to be performed in the pediatric patient. The methods that were used to carry out this case study were through objective and subjective data. We worked with a pediatric patient of male sex of 7 years of age, in the area of pediatrics in the city of Babahoyo, the data that was collected for the realization of the clinical case were by observation and the realization of the physical examination and those that we obtain through the interview, what the patient manifests or his relatives indicate us. The application of the nursing care process is one of the most important elements that should be carried out by the nursing professional since its preparation and execution will depend on the prompt recovery or deterioration of the patient's health status during their stay in the hospital